Analysis of issues and trends in timber and timber products trade flow situation in the Philippines - Segayo, Maria Lovella P.; Rotol, Luminda C.; Natividad, Mayumi Quintos; Cheng, Alex A.; Sibucao, Alejandrino R. Jr.; Maranon, Leyminda L. (2012)
The study analyzed the flow of timber and timber products among industry players, including the demand and supply, and identified the issues and bottlenecks in the trade flow and possible solutions to these problems.
A nationwide survey among different industry players such as the timber producers, processors, and end-users (i.e., households, construction firms) was conducted to acquire a better picture of the timber and timber trade flow situation in the country. Analysis showed that the weak trading situation and problems in the timber products flow are primarily caused by the limited access and sharing of information among industry players. There are also certain policies and regulatory issues that further aggravate the situation.
Perception of the industry players illustrates that there is a definite downward trend in the demand for lumber and supply of raw materials, yet majority of these players still foresee that the quality of local raw materials will remain the same or improve. Despite the negative views, it is apparent that majority of the industry players are still hopeful on the future of investing in plantation development.
Keywords: Timber; Forest products industry; Wood products -- Economic aspects; Lumber industry; Supply and demand